1,3,5-Triiodomesitylene - J.J. Meinnel, University of Rennes. (My University, 2008)
Inelastic Neutron Scattering spectrum of 1,3,5-Triiodomesitylene, C₉H₉I₃, measured on the TFXA instrument. 1,3,5-trimethyl-2,4,6-triiodobenzene.
Keywords: TFXA